GaN channel Nanoscale MOSFET with Silicon Source and Drain and Silicon Germanium Bulk - Das, Basab (International Journal of Computer Sciences and Engineering, 2025)
Extensive scaling in Conventional MOSFETs lead to degradation to their electrical parameters. This work proposes a GaN channel Nanoscale MOSFET for improvement in Electron Mobility, Off current with satisfactory On current, Threshold voltage and Subthreshold Swing Off current of the order of 10-11 A/um and Electron Mobility of around 1300 cm2/ V-s are obtained.